Client Self-Instruction: A Focus for Ethogenic Research - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2011)
Client self-instruction during counselling is proposed as an appropriate focus for ethogenic research. Such research would take the intentional actions of counsellors and clients as its primary subject matter, and would employ criteria of participant self-prediction and selfcontrol, and the validity criteria of researcher prediction and control. Philosophical and historical background of these ideas is summarized, and research questions, methods, and designs are proposed and illustrated. It is suggested that adoption of the theoretical and methodoligical perspectives presented might lead to a closer dialogue between scientists and practitioners in counselling psychology.